Student Teacher’s Reflective Skill: Phenomenology Study About the Experience of Teaching Practice in ESL Classrooms in a Primary School in Batam - Meri Fuji Siahaan (Bandar Lampung University (UBL), 2014)
Reflection is an important component of the teaching profession. It is the process of looking at information or events, evaluating them, and using the results to change or enhance future events. As teachers engage in reflection, they become more critical about their own teaching practices, consequently, they become more effective.This Phenomenology study explored the reflective skill of a student teacher during teaching practice in an ESL class in one of the primary schools in Batam. It was also aimed to see the impact of her reflective skill for her teaching practices. Instruments for data collection included reflection journal reviews and an interview. The study concluded that she reflected well on the students’ understanding of the material, consequently improving her teaching strategies. However, she did not reflect on how she handled her students ‘negative behaviour.